Botanical and genetic characterization of Mentha suaveolens Ehrh. cultivated in Egypt - El-Kashoury, E. S. A.; El-Askary, H. I.; Kandil, Z. A.; Salem, M. A.
This paper deals with the detailed botanical study of the stems and leaves of Mentha suaveolens Ehrh. (Labiatae), a highly valued medicinal and fragrant plant. Mentha suaveolens Ehrh. is useful as a carminative, antispasmodic, diaphoretic, analgesic, anti-inflammatory and antimicrobial drug. It is also useful in case of nausea, bronchitis and anorexia. Botanical investigation of Mentha suaveolens Ehrh has not been reported so far. Therefore, The macro- and micromorphological characteristics of the stems and leaves of Mentha suaveolens Ehrh. cultivated in Egypt are presented, with the aim of finding out the diagnostic characters for identification and differentiation of this species either in the entire or powdered forms. The major microscopic features of the stems and leaves are the presence of both glandular and non-glandular trichomes. Labiaceous glandular trichomes, a significant feature responsible for the secretion of volatile oil, are numerous on both stem and leaf surfaces. Also, the presence of diacytic stomata is another important diagnostic feature of the plant. Furthermore, the DNA of the plant was extracted and amplified using 10 decamer primers to reveal RAPD fragments. Each of the ten primers successfully directed the amplification of a genome-specific fingerprint of DNA fragment. A total of 65 different fragments have been generated by the two primers: OPC-07 and OPA-11 respectively, which can be used for the selective discrimination of M. suaveolens Ehrh. The highest numbers of fragments were 15 and 9 produced by the primers OPC-07 and OPA-11 respectively. The analysis of RAPD data, under the experimental conditions, can thus be used to distinguish the plant from other related species.
Keywords: DNA FINGERPRINTING; MACROMORPHOLOGICAL; MICROMORPHOLOGICAL; MINT